PENERAPAN MODEL PEMBELAJARAN KOOPERATIF POE (PREDICT-OBSERVE-EXPLAIN) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI IPA SMA NEGERI 2 PEKANBARU - Sari, Inda Purnama Sari Purnama (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to increase student achievement on the subject of solubility and solubility product in class XI IPA SMA Negeri 2 Pekanbaru. Form of research is experiment research with randomized control group pretest-posttest design. The sample consisted of two classes, XI IPA3 as an experiment class and XI IPA4 as a control class randomly selected after tests of normality and homogeneity. Experiment class was given implementing cooperative learning POE (Predict-Observe-Explain), while the control class wasnot given implementing cooperative learning POE (Predict-Observe-Explain). Data analysis technique is used t-test. Based on the results of final processing data use t-test formula obtained tcount > ttable is 2,78 > 1,67, it means that the applying of cooperative learning POE (Predict-Observe-Explain) can improve student achievement on the subject of solubility and solubility product in class XI IPA SMA Negeri 2 Pekanbaru. with the increasing percentage of 9.94 %. Keywords : Cooperative Learning, POE (Predict-Observe-Explain), Learning Achievement.